Pro Durian - Durian Farm Threats Identification Using Image Recognition - Yusoff, Aiman; Kamarudin, Noraziahtulhidayu (Applied Information Technology And Computer Science, 2022)
Pro Durian – A durian farm threats identification that uses image recognition and gives information on durian farm threats animals. The main objective of this research is to develop a mobile app for durian farming with animal threats alert features. This application contains two main modules which is image recognition modules that is focusing on animal detection with an alert feature to drive away those animals, while additional information modules focus on giving information to the users on each durian farm threat. Multimedia Development Life Cycle (MDLC) is used as the methodology to develop the recognition apps The result from the alpha testing shows the app work as it should in each of the test cases. Furthermore, in the beta testing which was participated by 10 testers, the questionnaire received a percentage of 85% user acceptance. However, there are a few improvements that can be done in the future.